Analysis of the Implementation of Blockchain Technology in Optimizing Crypto Inventory Through the Supply Chain Management Method - Amin, Roihanul Falakil (Information Technology and Systems, 2024)
This study examines how the application of the Supply Chain Management (SCM) method to cryptocurrency inventory management can be optimized with blockchain technology. It is believed that blockchain, which is known for being transparent, secure, and effective, will increase operational effectiveness and lower risks in the administration of cryptocurrency inventory. It focuses on five key factors, namely transparency, data security, transaction speed, operational efficiency, and cost reduction. The study looks at the potential effects of each blockchain feature on cryptocurrency inventory management. Questionnaires on cryptocurrency users, miners, and investors are used to collect relevant data, and literature. The findings show how the application of blockchain technology lowers operational costs, increases transparency, and speeds up transactions to dramatically improve the efficiency of crypto inventory management. The findings claim that the application of blockchain technology through Supply chain management (SCM) not only adds value in terms of security and reliability, but also allows cryptocurrency companies to respond to market demand more quickly. This study adds to our understanding of how blockchain technology is used in the digital finance industry, particularly as it relates to crypto asset inventory management